The global burden of cataracts and its attributable risk factors in 204 countries and territories: a systematic analysis of the global burden of disease study - Wang, Dongyue; Tang, Tong; Li, Peiheng; Zhao, Jing; Shen, Bairong; Zhang, Ming (Frontiers in Public Health, 2024)
Introduction The global distribution and trends in the attributable burden of cataract risk have rarely been systematically explored. To guide the development of targeted and accurate cataract screening and treatment strategies, we analyzed the burden of cataract disease attributable to known risk factors. Method This study utilized detailed cataract data from the Global Burden of Disease e 2019, and we analyzed disability-adjusted life years (DALYs) e each risk factor from 1990 to 2019. Additionally, we calculated estimated annual percentage changes (EAPCs) during the study period. Results The results revealed that from 1990−2019, the global age-standardized DALYs of e attributable to particulate matter pollution, smoking, high fasting glucose plasma and high BMI showed steady downward trends (1990−2009: EAPC = −0.21 [−0.57 −0.14]); 2000−2009: EAPC = −0.95 [−1.01 −0.89]; 2010−2019: EAPC = −1.41 [−1.8 −1.02]). The age-standardized DALYs and mortality caused by each risk factor were highest in the low-middle sociodemographic index (SDI) region (EAPC = −1.77[(−2.19–−1.34)]). The overall disease burden of cataracts is lower in males than in females. When analyzing the EAPCs of cataract disease burden for each risk factor individually, we found that the age-standardized disability-adjusted life years caused by particulate matter pollution and smoking decreased (PMP1990-2009: EAPC = −0.53 [−0.9–−0.16]; 2000−2009: EAPC = −1.39 [−1.45--1.32]; 2010−2019: EAPC = −2.27 [−2.75–−1.79]; smoking 2000 to 2009: EAPC = −1.51 [−1.6–−1.43], 2009 to 2019: EAPC = −1.34 [−1.68–−1])), while high fasting plasma glucose and high body mass index increased annually (HFPG1990 to 1999: EAPC = 1.27 [0.89−1.65], 2000 to 2009: EAPC = 1.02 [0.82−1.22], 2010−2019: EAPC = 0.44 [0.19−0.68]; HBMI 1990 to 1999: EAPC = 1.65 [1.37−1.94], 2000 to 2009: EAPC = 1.56 [1.43−1.68], 2010−2019: EAPC = 1.47 [1.18−1.77]). Disscussion The burden of cataracts caused by ambient particulate matter and smoking is increasing in low, low-middle SDI areas, and specific and effective measures are urgently needed. The results of this study suggest that reducing particulate matter pollution, quitting smoking, controlling blood glucose, and lowering BMI could play important roles in reducing the occurrence of cataracts, especially in older people.